Disaster risk management system in Vietnam: progress and challenges - Tran Thi Lan Huong; Duong Thi Van Anh; Tran Tho Dat; Dinh Duc Truong; Duong Duc Tam (Heliyon, 2022)
Background: Vietnam is one of the countries most impacted by disasters in Asia- Pacific. Floods, droughts and storms are the most common catastrophes. These risks endanger millions of lives and create massive financial and production losses. Objective: This study aims at reviewing the disaster risk management (DRM) system in Vietnam, identifying progress and challenges of this system, hence making recommendations for improving the system for better responding with natural hazards. Method: The study uses PSR model (Pressure- State- Response) in combination with DRM management framework by United Nations Development Program (UNDP) to evaluate DRM system in Vietnam with 5 aspects: (i) DRM regulatory framework (ii) DRM organization (iii) DRM financial resources (iv) DRM integration in to plans at central and local levels (v) Disaster warning and education. The data collection consists of reviewing existing literature and interviewing key informants in DRM. Results: Disasters is a serious threat to Vietnam’s socio economic development. To respond, Vietnam has made many efforts including develop a comprehensive legal framework for DRM which Law on Disaster Prevention and Control takes the key role. Vietnam has also established a fairly well organized DRM system from the central to local levels. The financial sources for DRM are arranged from State budget and sources outside State budget. Vietnam has developed major policies for integrating DRM into development plans centrally and locally. The disaster information and warning system is being modernized with the integration of disaster education in training programs. Challenges in DRM are identified, including institutional, financial and information issues. In addition, Vietnam is facing the increase of disasters and extreme climate events due to climate change. Covid 19 and its socio-economic consequences also lead to a lack of resources for DRM. Economic development moreover results in the decline of ecosystem-based disaster mitigation works and put more pressures on DRM. Recommendations: In the future, Vietnam should develop an information-sharing network between ministries, sectors, localities and NGOs to support the policy formulation process and enhance the coordination of multi-stakeholders. The country should also establish more proper funding allocation mechanisms to fulfill DRM’s demands, especially for disaster preparedness and reconstruction phases.